Effect of power variation on microstructure and surface morphology of HgCdTe films deposited by RF magnetron sputtering - 王光华 孔金丞 李雄军 邱锋 李悰 杨丽丽 孔令德 姬荣斌 (Journal of semiconductors, 2010)
Mercury cadmium telluride films were grown by the RF magnetron sputtering technique at different sputtering powers.In experiment,X-ray diffraction（XRD） and atomic force microscopy（AFM） have been used to characterize the microstructure of HgCdTe films.The experimental results showed that when the growth power increased,the growth rate of HgCdTe films increased;when the growth power was less than 30 W,the HgCdTe film deposited by RF magnetron sputtering was amorphous;when the growth power was more than 30 W,the films exhibited polycrystalline structure.Films deposited at different growth rates were found to have characteristically different formations and surface morphologies;as observed through AFM,the surface morphology is composed of longitudinal islands forming a maze-like pattern in the high deposition rate.AFM analysis also illustrated that a significant reduction in the areal density of large islands and characteristically smoother films was achieved using a low deposition rate.